Relationship of Hyperglycaemia, Hypoglycaemia, and Glucose Variability to Atherosclerotic Disease in Type 2 Diabetes - Caroline Jane Magri; Dillon Mintoff; Liberato Camilleri; Robert G. Xuereb; Joseph Galea; Stephen Fava (Journal of Diabetes Research)
Objective. Type 2 diabetes mellitus (T2DM) is known to be associated with increased cardiovascular risk. The aim of this study was therefore to investigate the independent effects of hyperglycaemia, hypoglycaemia, and glucose variability on microvascular and macrovascular disease in T2DM. Methods. Subjects with T2DM of <10 years duration and on stable antiglycaemic treatment underwent carotid intima-media thickness (CIMT), ankle-brachial index (ABI), albumin-creatinine ratio (ACR), and HbA1c measurement, as well as 72-hour continuous glucose monitoring. Macrovascular disease was defined as one or more of the following: history of ischaemic heart disease (IHD), cerebrovascular accident (CVA), ABI < 0.9, or abnormal CIMT. Results. The study population comprised 121 subjects with T2DM (89 males : 32 females). The mean age was 62.6 years, and the mean DM duration was 3.7 years. Macrovascular disease was present in 71 patients (58.7%). In multivariate logistic regression analysis, body surface area (BSA) (OR 18.88 (95% CI 2.20–156.69), p=0.006) and duration of blood glucose (BG) < 3.9 mmol/L (OR 1.12 (95% CI 1.014–1.228), p=0.024) were independent predictors of macrovascular disease. BSA (OR 12.6 (95% CI 1.70–93.54), p=0.013) and duration of BG < 3.9 mmol/L (OR 1.09 (95% CI 1.003–1.187), p=0.041) were independent predictors of abnormal CIMT. Area under the curve for BG > 7.8 mmol/L (β = 15.83, p=0.005) was the sole independent predictor of albuminuria in generalised linear regression. Conclusions. This study demonstrates that hypoglycaemia is associated with the occurrence of atherosclerotic disease while hyperglycaemia is associated with microvascular disease in a Caucasian population with T2DM of recent duration.